A Healthy Lifestyle Offsets the Increased Risk of Childhood Obesity Caused by High Birth Weight: Results From a Large-Scale Cross-Sectional Study - Zheng-he Wang (Frontiers Media S.A., 2021)
Objective: To investigate whether a healthy lifestyle is associated with the lower childhood obesity regardless of birth weight.Methods: Participants were selected from a large-scale cross-sectional study conducted in the seven provinces across China. Birth weight and lifestyle factors were collected through a questionnaire. A weighted healthy lifestyle score was calculated and categorized into favorable, intermediate, and unfavorable lifestyles.Results: A total of 47,768 participants were enrolled in this study. Overall, 16.4% of the participants followed a favorable lifestyle, 62.8% followed an intermediate lifestyle, and 20.8% followed an unfavorable lifestyle. Compared with the participants who were born normal birth weight (NBW), participants who were born high birth weight (HBW) (OR = 1.58; 95% CI 1.48–1.77) and very high birth weight (VHBW) (OR = 1.79; 95% CI: 1.47–2.18) had higher obesity risk, however, the participants who were born low birth weight (LBW) had lower obesity risk (OR = 0.81; 95% CI: 0.68–0.96). Participants with an unfavorable lifestyle were associated with a higher risk of childhood obesity compared with the participants with favorable lifestyle (OR = 1.25; 95%CI: 1.14–1.38). Participants who were born VHBW and with an unfavorable lifestyle had 2.76 times (95% CI: 1.78–4.28) further risk of childhood obesity compared with the participants who were born NBW and with a favorable lifestyle. However, adherence to a favorable lifestyle seems to counteract the elevated risk of childhood obesity by VHBW (OR = 1.37; 95% CI: 0.84–2.24).Conclusion: Both the HBW and unfavorable lifestyle were significantly associated with risk of childhood obesity. Adherence to a favorable lifestyle decreased the risk of childhood obesity among the participants with VHBW. A more longitudinal study is required to repeat the finding to inform tailored prevention programs.